1993
DOI: 10.1177/41.12.8245432
|View full text |Cite
|
Sign up to set email alerts
|

Significance of high glucose-6-phosphatase activity in rat oviduct epithelium.

Abstract: To study the origin of glucose in the oviduct fluid, we cytochemidy examined gIucose-6-phasphatase (G6Pase) activity in rat oviduct. The activity in the whole oviduct was also assayed biochemically. During proestrous, estrous, and metestrous phases, staining reaction for the activity was moderate in the epithelium of the caudal isthmus (Cd) and uterotubal junction (UJ), whereas it was weak in that of the ampulla (A) and cephalic isthmus (CeI). In the diestrous phase, staining reaction in the epithelium of CaI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…8). The current result revealed marked development and growth of uterine gland which are also recorded at functional status of uterus by (7,19). The finding revealed that the endometrium and myometrium thickness were significantly increased during late pregnancy as compared to other results recorded by (6,10) in not pregnant rabbits and rat respectively, this was associated with increase in population of uterine glands and sizes of muscle fibers of myometrium, similar finding are reported in the humans (20,21).…”
Section: Uterussupporting
confidence: 84%
“…8). The current result revealed marked development and growth of uterine gland which are also recorded at functional status of uterus by (7,19). The finding revealed that the endometrium and myometrium thickness were significantly increased during late pregnancy as compared to other results recorded by (6,10) in not pregnant rabbits and rat respectively, this was associated with increase in population of uterine glands and sizes of muscle fibers of myometrium, similar finding are reported in the humans (20,21).…”
Section: Uterussupporting
confidence: 84%
“…Tissue group I comprises tissues that are continuously exposed to various chemical and mechanical stresses including cardiac myocytes, hepatocytes, epithelial cells of the intestine, and the ciliated epithelial cells of the oviduct. These cells need large amounts of energy to participate in the extensive exchange of ions, nutrients, hormones, and cytokines [ 1 , 3 , 8 , 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%